PARAMETER KEBENARAN ILMU PENGETAHUAN (SAINS) DALAM AL-QUR’AN - Endah Tri Wisudaningsih; Musyafi’ (UNZAH Genggong, 2020)
The truth of a science can truly be known. Truth is the culmination of the study of epistemology which boils down to metaphysics. The essence of a scientific truth is the compatibility of information, or theory with the reality of the object itself. In aspects of the metaphysical world and absolute reality transcendental, the truth parameter is the text of revelation (al-Qur'an and Hadith) whose meaning is known exactly according to the standard of Ijma 'and logic for the degree of